A GATA3 gene mutation that causes incorrect splicing and HDR syndrome: a case study and literature review - Tao, Yilun; Yang, Lin; Han, Dong; Zhao, Chen; Song, Wenxia; Wang, Haiwei; Li, Xiaoze; Wang, Lihong (Frontiers in Genetics, 2023)
Hypoparathyroidism, deafness, and renal dysplasia (HDR) syndrome is an infrequent autosomal dominant genetic disorder caused by haploinsufficiency of the GATA binding protein 3 (GATA3) gene. In this report, we present a case study of a 6-year-old female patient manifesting seizures, tetany, hypoparathyroidism, and sensorineural hearing loss. A heterozygous variant, c.1050+2T>C, in the GATA3 gene was discovered by genetic testing. Moreover, a minigene splicing experiment revealed that the aforementioned variation causes incorrect splicing and premature cessation of protein synthesis. The clinical profile of the patient closely resembles the well-known phenomenology of HDR syndrome, supporting the association between the condition and the GATA3 variant. The challenges in early diagnosis highlight the importance of employing next-generation sequencing for timely detection of rare diseases. Additionally, this research contributes to a deeper understanding of the genotype-phenotype correlations in HDR syndrome, underscoring the critical need for improved diagnostic and therapeutic strategies.